Fall 2009/JonathanS: Difference between revisions
No edit summary |
|||
Line 1: | Line 1: | ||
== Problem == |
== Problem == |
||
A simple pendulum with a length L = 0.5m is pulled back and released from an initial angle <math>\theta_0 = 12^o</math>. Find an equation that gives the angle of the pendulum at any given time '''t'''. |
A simple pendulum with a length L = 0.5m is pulled back and released from an initial angle <math>\theta_0 = 12^o</math>. Then it is run with a forcing function of cos(3<math>\theta</math>) Find an equation that gives the angle of the pendulum at any given time '''t'''. |
||
== Solution == |
== Solution == |
||
Assuming no damping and a small angle(<math>\theta < 15^o</math>), the equation for the motion of a simple pendulum can be written as |
Assuming no damping and a small angle(<math>\theta < 15^o</math>), the equation for the motion of a simple pendulum can be written as |
||
:<math>{\mathrm{d}^2\theta\over \mathrm{d}t^2}+{g\over \ell}\theta= |
:<math>{\mathrm{d}^2\theta\over \mathrm{d}t^2}+{g\over \ell}\theta=cos(3\theta).</math> |
||
Substituting values we get |
Substituting values we get |
||
:<math>{\mathrm{d}^2\theta\over \mathrm{d}t^2}+{9.81\over 0.5}\theta= |
:<math>{\mathrm{d}^2\theta\over \mathrm{d}t^2}+{9.81\over 0.5}\theta=cos(3\theta).</math> |
||
<math>\Rightarrow{\mathrm{d}^2\theta\over \mathrm{d}t^2}+{19.62}\theta= |
<math>\Rightarrow{\mathrm{d}^2\theta\over \mathrm{d}t^2}+{19.62}\theta=cos(3\theta).</math> |
||
Line 22: | Line 22: | ||
Now we can take the Laplace Transform to change the second order differential equation, from the t domain, into a simple linear equation, from the s domain, that's much easier to work with |
Now we can take the Laplace Transform to change the second order differential equation, from the t domain, into a simple linear equation, from the s domain, that's much easier to work with |
||
:<math>\mathcal{L}\bigg\{{\mathrm{d}^2\theta\over \mathrm{d}t^2}+{19.62}\theta\bigg\}=s^2F(s)-sf(0)-f^{ '}(0)+{19.62}\theta= |
:<math>\mathcal{L}\bigg\{{\mathrm{d}^2\theta\over \mathrm{d}t^2}+{19.62}\theta\bigg\}=s^2F(s)-sf(0)-f^{ '}(0)+{19.62}\theta=\mathcal{L}\{cos(3\theta)\}</math> |
||
<math>\Rightarrow</math> <math> s^2\boldsymbol{\theta}-s\theta(0)-\theta^{ '}(0)+{19.62}\boldsymbol{\theta}= |
<math>\Rightarrow</math> <math> s^2\boldsymbol{\theta}-s\theta(0)-\theta^{ '}(0)+{19.62}\boldsymbol{\theta}={s\over {s^2+1}} \,</math> |
||
Since we know that <math>\theta(0)=12^o</math> and the initial velocity <math>\theta^{ '}(0)=0</math> we get |
Since we know that <math>\theta(0)=12^o</math> and the initial velocity <math>\theta^{ '}(0)=0</math> we get |
||
:<math>s^2\boldsymbol{\theta}-12s+19.62\boldsymbol{\theta}= |
:<math>s^2\boldsymbol{\theta}-12s+19.62\boldsymbol{\theta}={s\over {s^2+1}} \,</math> |
||
<math>\Rightarrow</math> <math>\boldsymbol{\theta}(s^2+19.62)=12s \,</math> |
<math>\Rightarrow</math> <math>\boldsymbol{\theta}(s^2+19.62)={s\over {s^2+1}}+12s \,</math> |
||
<math>\Rightarrow</math> <math>\boldsymbol{\theta}={12s\over {s^2+ |
<math>\Rightarrow</math> <math>\boldsymbol{\theta}(s^2+19.62)={s\over {s^2+1}}+{12s(s^2+1)\over {s^2+1}} \,</math> |
||
<math>\Rightarrow</math> <math>\boldsymbol{\theta}={12s\over {s^2+ |
<math>\Rightarrow</math> <math>\boldsymbol{\theta}(s^2+19.62)={s(12s^2+13)\over {s^2+1}} \,</math> |
||
<math>\Rightarrow</math> <math>\boldsymbol{\theta}={s(12s^2+13)\over {(s^2+19.62)(s^2+1)}}</math> |
|||
Revision as of 10:56, 28 October 2009
Problem
A simple pendulum with a length L = 0.5m is pulled back and released from an initial angle . Then it is run with a forcing function of cos(3) Find an equation that gives the angle of the pendulum at any given time t.
Solution
Assuming no damping and a small angle(), the equation for the motion of a simple pendulum can be written as
Substituting values we get
Remember the identities
Now we can take the Laplace Transform to change the second order differential equation, from the t domain, into a simple linear equation, from the s domain, that's much easier to work with
Since we know that and the initial velocity we get
Now we can take the inverse Laplace Transform to convert our equation back into the time domain using the identity
We get
This will give us the angle (in degrees) of the pendulum at any given time t.
Initial Value Theorem
We can use the Initial Value Theorem as a check that our initial values for the problem are valid.
Below we will use this theorem to check the values for our problem.
This value is the initial angle we gave the pendulum so it checks out.
Final Value Theorem
We can use the Final Value Theorem as a check that our final values for the problem are valid.
Below we will use this theorem to check the values for our problem.
This is zero because the average angle as time goes to infinity will be zero (halfway between -12 and 12 degrees).